European energy security in the context of the U.S. external energy policy - Sargsyan, Tigran (YSU Journal of International Affairs, 2022)
The article discusses the main aspects of European energy security and the U.S. perspectives (engagement and interests). Therefore, the brief theoretical framework of energy policy and energy security is presented in the beginning through summarizing and generalizing a number of theoretical definitions. Afterwards, on the base of relevant statistical data analysis and summarizing the main contemporary issues towards ensuring European Union’s (EU) energy security are referred to: lack of own fuel and energy resources (particularly in the face of growing demand), predominance of imported energy in the overall structure of energy consumption (external energy dependence), the large share of a limited number of external energy suppliers. In the context of the above mentioned issues and challenges, the main priorities and ways of U.S. involvement and contribution to European energy security are revealed, grouped and analyzed in a systemized manner: supporting the further regional diversification of the EU’s energy import, legislative, institutional and financial support, providing with direct energy alternatives (particularly, liquefied natural gas), etc.